IMPLEMENTASI ASAS KECERMATAN JAKSA DALAM PENEGAKAN HUKUM DI INDONESIA GUNA MEWUJUDKAN GOOD GOVERNANCE - Rahmahani, Adhining; Wardhani, Sri Pramudya (Lex Jurnalica, 2026)
AbstractThe purpose of this study is to determine whether a Prosecutor who incorrectly drafts an indictment violates the Prosecutor's Code of Ethics and to examine the implementation of the principle of accuracy a component of the General Principles of Good Administration (AUPB) by Prosecutors in Indonesian law enforcement to achieve Good Governance. The research method used a normative legal research approach with secondary data relevant to the related issues and utilized additional data in the form of guided free interviews with Prosecutors. The results of the study showed that errors in drafting an indictment (specifically the lack of synchrony between criminal events and charges) fell under the criteria of violating core ethical values, namely integrity, professionalism, and wisdom. This meant that the Prosecutor did not uphold the principles of a constitutional state. Furthermore, the actions of the Prosecutor as a state administrator who erred in drafting the indictment did not implement the unwritten norm of the principle of accuracy, which is part of the General Principles of Good Administration (AUPB). In conclusion, a Prosecutor who drafts an incorrect indictment violates the code of ethics regarding core values such as integrity, professionalism, and wisdom, and fails to implement the principle of accuracy required for good governance. Keywords: Rule of Law, Principle of Accuracy, Good Governance. AbstrakTujuan penelitian ini ialah untuk mengetahui Jaksa yang salah menyusun surat dakwaan melenggar atau tidak dari sisi kode etik Kejaksaan dan implementasi asas kecermatan yang merupakan AUPB oleh Jaksa dalam penegakan hukum di Indonesia guna mewujudkan Good Governance. Metode penelitian ini menggunakan metode penelitian yurudis normatif dengan menggunakan data sekunder yang releban dengan permasalahan yang terkait dan menggunakan data tambahan berupa wawancara bebas terpimpin dengan Jaksa. Hasil penelitian bahwa dalam kesalahan membuat surat dakwaan (tidak sinkron peristiwa pidana dengan tuntutan) oleh Jaksa maka masuk kriteria pelanggaran kode etik nilai keutamaan yakni integritas, profesionalitas dan kebijaksanaan yang berarti Jaksa tidak menjalankan prinsip negara hukum. Selain itu tindakan Jaksa selaku administrator negara yang salah dalam menyusun surat dakwaan tidak mengimplementasikan norma tidak tertulis yakni asas kecermatan yang merupakan salah satu Asas-asas Pemerintahan yang Baik (AUPB) guna mewujudkan good governance. Jaksa yang membuat surat dakwaan telah melanggar kode etik berupa nilai keutamaan seperti integrtas, profesionalitas dan kebijaksanaan serta tidak menjalankan asas kecermatan.Kata kunci : Negara Hukum, Asas Kecermatan, Good Governance